The importance of differentiation for organizational ambidexterity - Fumie Ando; Yumi Tonan; Keisuke Tomata (Annals of Business Administrative Science)
Several companies aspire to organizational ambidexterity; however, achieving it requires overcoming certain hurdles. With regard to simultaneous or structural ambidexterity, which large companies tend to adopt, the challenges associated with of integrating physically separated units into existing units or core business activities is often discussed. However, Japanese companies with high internal homogeneity fail to transition to subsequent phases and achieve the desired ambidexterity. This is not due to difficulties with integration but insufficient differentiation in the early stages. The case of Company A, a large Japanese software company examined in this paper, is a typical example of this problem. If it were possible to assess in advance whether differentiation is sufficient, and identify which aspects are lacking, we could prevent setbacks in the process and increase the feasibility of achieving organizational ambidexterity. Therefore, this paper proposes the use of the integrated N-T model (Ando, 2023) as a supportive tool for this purpose.